Ventilación mecánica prolongada como factor de riesgo para Displasia Broncopulmonar en neonatos prematuros - Cabrera Rojas, Lizbeth Alexandra Jannette (2021)
Bronchopulmonary dysplasia (BPD) is a frequent pathology observed in extreme preterm neonates and those with very low weight at birth. This population group often requires invasive ventilatory support, which has an important impact on the neonate’s respiratory function prognosis. Therefore, the objective of this investigation proyect is to determine if prolonged mechanical ventilation is a risk factor for bronchopulmonary dysplasia in preterm neonates by the review of medical records of preterm neonates attended at the Neonatology department of Hospital Regional Docente de Trujillo during the period of January 2018 to December 2018 by a retrospective, analytic, observational case – control study.